Digitalization of Intangible Cultural Heritage (ICH) Archives As Legal Protection of Intellectual Property Rights - Amri Hariri (Program Studi Ilmu Perpustakaan UIN Alauddin, 2021)
Digitizing (ICH) archives is an important thing in the digital era. These archives are national cultures that must be protected and preserved and could not be claimed by foreign parties. This study aims to find out the importance of ICH archives as legal protection for IPR. The design of this research is a literature review. The data sources were scientific journal articles, books, and documents from trusted organizations. To analyze the data, the researcher uses the content analysis method to analyze the text objectively and validly. The results of this study answer four important issues, namely (1) digitization archive can be done by referring to IFLA policies; (2) ICH archives can be used for IPR submission in the communal ownership field; (3) digitizing ICH archives have an important role in efforts to maintain the national culture, legal protection, security, providing public access, make the archive re-saving process more manageable, and saving maintenance costs; (4) legal protection of ICH can be achieved in four ways, namely through customary law, registered as IPR, recording, and stipulation of ICH by the Ministry of Education and Culture of the Republic of Indonesia, the stipulation of UNESCO ICH as a representation of world recognition. Those whole processes are a preventive measure to prevent discrimination and unilateral claims to achieve prosperity and legal justice.